Bilateral early activation of retinal microglial cells in a mouse model of unilateral laser-induced experimental ocular hypertension. (June 2018) - de Hoz, Rosa; Ramírez, Ana I.; González-Martín, Rosa; Ajoy, Daniel; Rojas, Blanca; Salobrar-Garcia, Elena; Valiente-Soriano, Francisco J.; Avilés-Trigueros, Marcelino; Villegas-Pérez, Maria P.; Vidal-Sanz, Manuel; Triviño, Alberto; Ramírez, José M.; et al.
Abstract: The immune system plays an important role in glaucomatous neurodegeneration. Retinal microglial reactivation associated with ganglion cell loss could reportedly contribute to the glaucoma progression. Recently we have described signs of microglia activation both in contralateral and ocular hypertension (OHT) eyes involving all retinal layers 15 days after OHT laser induction in mice. However, no works available have analyzed the microglial activation at earliest time points after OHT induction (24 h) in this experimental model. Thus, we seek to describe and quantify signs of microglia activation and differences depending on the retinal layer, 24 h after unilateral laser-induced OHT. Two groups of adult Swiss mice were used: age-matched control (naïve) and lasered. In the lasered animals, OHT eyes as well as contralateral eyes were analyzed. Retinal whole-mounts were immunostained with antibodies against Iba-1 and MHC-II. We quantified the number of microglial cells in the photoreceptor layer (OS), outer plexiform layer (OPL), and inner plexiform layer (IPL); the number of microglial vertical processes connecting the OPL and OS; the area of the retina occupied by Iba-1+ cells (Iba1-RA) in the nerve fiber layer-ganglion cell layer (NFL-GCL), the total arbor area of microglial cells in the OPL and IPL and; Iba-1+ cell body area in the OPL, IPL and NFL-GCL. In contralateral and OHT eyes the morphological features of Iba-1+ cell activation were: migration, enlargement of the cell body, higher degree of branching and reorientation of the processes, radial disposition of the soma and processes toward adjacent microglial plexuses, and presence of amoeboid cells acting as macrophages. These signs were more pronounced in OHT eyes. Most of Iba-1+ cells did not express MHC-II; rather, only dendritic and rounded cells expressed it. In comparison with naïve eyes, in OHT eyes and contralateral eyes no significant differences were found in the microglial cell number; but there was a significant increase in Iba1-RA. The total arbor area of microglial cells was significantly decreased in: i) OHT eyes with respect contralateral eyes and naïve-eyes in IPL; ii) OHT eyes with respect to naïve eyes in OPL. The number of microglial vertical processes connecting the OPL and OS were significantly increased in contralateral eyes compared with naïve-eyes and OHT eyes. In OPL, IPL and NFL-GCL, the cell body area of Iba-1+ cells was significantly greater in OHT eyes than in naïve and contralateral eyes, and greater in contralateral eyes than in naïve eyes. A non-proliferative microglial reactivation was detected both in contralateral eyes and in OHT eyes in an early time after unilateral laser-induced OHT (24 h). This fast microglial activation, which involves the contralateral eye, could be mediated by the immune system. Highlights: 24 h after laser-induced OHT, a non-proliferative microglial reactivation was shown in OHT eyes. 24 h after laser-induced OHT, a non-proliferative microglial reactivation was shown in contralateral untreated eyes. This fast microglial activation in both eyes could be mediated by the immune system.